Are US antidumping cases being crowded out by other forms of protectionism?. Issue 1 (16th January 2020) - Desai, Prashant; Feinberg, Robert M.
Abstract : Purpose: The issue of substitutability between various modes of import protection has been studied by economists in various ways. Since President Donald Trump came into office and soon started imposing tariffs, the need by US firms to file antidumping (AD) cases would seem to have been reduced. This study aims to examine whether such a reduction in AD cases has occurred. Design/methodology/approach: Quarterly US AD filings via a negative binomial regression analysis are explained. Patterns based on data from 1995 through 2016 are obtained first and then predict US AD petitions for 2017 and 2018. Findings: The authors reject a hypothesis of substitution away from AD in the Trump era of general protectionism but do find some support for the notion that protection moves downstream, with greater than predicted AD filings in downstream metals sectors. Originality/value: This is the first study to examine the possibility of trade policy substitutability in the Trump era.